Emission and control of nitrous oxide from a biological wastewater treatment system with intermittent aeration - Park, KY; Inamori, Y; Mizuochi, M; Ahn, KH (SOC BIOSCIENCE BIOENGINEERING JAPAN, 2000)
Nitrous oxide (N2O) can be emitted as a by-product of the process of nitrogen removal from wastewater. Two methods of complete denitrification and media application were studied in lab-scale intermittent aeration reactors fed with domestic wastewater to refine methods of controlling the N2O emission rate. A study on cyclic patterns showed that the highest N2O emission rate was at the beginning of the aerobic phase rather than the anoxic: phase. This was probably because the nitrifying bacteria had accumulated nitrite nitrogen (NO2-) under low DO conditions. Methanol as an external carbon source was added during the anoxic phase to reduce nitrate nitrogen (NO3-) when denitrification was completed. The N2O emission rates in both the aerobic and anoxic phases were significantly influenced by residual NO3-, increasing monotonically as the concentration of NO3- in the reactor increased. Over 95% of average N2O emissions in both the aerobic and anoxic phases were prevented when methanol was added. The biofilm reactor showed similar patterns to those of the non-biofilm reactor in track behavior, but the former was more effective in the reduction of N2O emissions.
Keywords: DENITRIFYING ACTIVATED-SLUDGE; NITROSOMONAS-EUROPAEA; ALCALIGENES-FAECALIS; WATER TREATMENT; TREATMENT-PLANT; N2O PRODUCTION; NITRIFICATION; DENITRIFICATION; GAS